Research and conservation in Marina el-Alamein in 2016 (Polish–Egyptian Conservation mission) - Rafał Czerner; Grażyna Bąkowska-Czerner; Wiesław Grzegorek; Piotr Zambrzycki (Polish Archaeology in the Mediterranean, 2017)
Activities undertaken by the Polish–Egyptian Conservation Mission to Marina el-Alamein in 2016 included research and conservation in the public district of the ancient town as well as in private houses. Work focused foremost on research, conservation and exhibition of monuments in the central town square, especially the remains of a peristyle adjacent from the east, and the southern portico of the square itself. Research and conservation continued also in the area north of the central square, concentrating on the remains of public baths dating from the Hellenistic period and, on the south, on the remnants of Roman baths in use from the 2nd to the 3rd century AD. Maintenance conservation was carried out in private houses, in both baths complexes and in the eastern and southern area of the central square.